Pengaruh Stress terhadap Prestasi Kerja dan Beban Kerja - Muhammad Amtsaludin Imsadi (Jurnal Bintang Manajemen, 2024)
Employees experiencing work-related Stress tend to exhibit lower job performance due to difficulties in focusing and insufficient energy to complete tasks. This study aims to understand the influence of work-related Stress and workload on job performance at PT. Cicurug Anugrah Raharja. The research employs a quantitative approach with a survey method. The population consists of all employees at PT. Cicurug Anugrah Raharja, with a sample size of 20 individuals selected randomly using purposive sampling technique. Data analysis was conducted using linear regression. The results indicate a significant positive correlation between work-related Stress and workload (r = 0.446, p = 0.049). However, there was insufficient evidence to support a significant influence of work-related Stress or workload on job performance in this sample. In conclusion, while there is a relationship between work-related Stress and workload with job performance, other factors may also play a role in influencing employee performance at PT. Cicurug Anugrah Raharja.